Synthesis of cyanato-functional polymaleimides and their application in negative-tone photoimaging by post-crosslinking - Lee, Chan Woo; Kim, Jun Woo; Lee, Jae-Hyoung; Ahn, Kwang-Duk (ELSEVIER SCIENCE BV, 2009)
A cyanato-functional maleimide monomer (CyOPMI) was radically copolymerized with N-[4-(tetrahydropyranyloxy)phenyl]maleimide (THPPMI) and methyl methacrylate (MMA) to obtain reactive cyanate polymers along with acid-labile THP-protecting groups. The soluble copolymers of CyOPMI employed, as cyanato-imidopolymers, were converted to the insoluble polymers by thermal or photo-acid treatment based on the acid-catalyzed deprotection of THP groups and cyclotrimerization of the pendent cyanto groups to form a crosslinked triazine structure (cyanurate). Upon this selective post-crosslinking, the cyanato-polymers were applied to negative-tone photoimaging by photolithography. CyOPMI was radically copolymerized with various vinyl monomers such as MMA, styrenes (St) and alkyl vinyl ethers (R'VE) to obtain soluble polymers by controlling the monomer feed ratios and polymerization conditions. The high thermal properties of the cyanato-imido polymers were attributed to the curing characteristics of the pendant cyanatophenyl and imidophenolic groups. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: PHOTOCHEMICAL ACID GENERATION; PROTECTED BLOCK-COPOLYMERS; BIFUNCTIONAL MALEIMIDES; CHEMICAL AMPLIFICATION; RESIST MATERIALS; ESTER RESINS; POLYMERIZATION; POLYMERS; SYSTEMS; PHOTOPOLYMERIZATION